New, potent, small molecule agonists of tyrosine kinase receptors attenuate dry eye disease - Yu, Zhiyuan; Joy, Shaon; Mi, Tianxiong; Yazdanpanah, Ghasem; Burgess, Kevin; de Paiva, Cintia S. (Frontiers in Medicine, 2022)
Nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), and neurotrophin3 (NT-3) bind to tyrosine kinase (Trk) receptors, TrkA, TrkB, and TrkC, respectively. This study investigated the efficacy of novel molecule agonists of Trk receptors in an in vivo model of dry eye disease (DED). Small molecule TrkC agonist C1) and a pan-Trk agonist (pan) were synthesized for this. C57BL/6J mice were subjected to desiccating stress (DS) and received bilateral eye drops of C1, pan, or vehicle (2x/day). Dry eye signs, inflammation and expression of Corneal barrier function, and conjunctival goblet cell (GC) densities were measured as part of the DED phenotype. Corneal epithelial lysates were collected for either western blot or RNA extraction. Extracted total RNAs were used for NanoString analyses. Immunofluorescent staining was performed on wholemount corneas using anti-TNFAIP3 and anti-EP4 antibodies. Compared to vehicle, mice subjected to desiccating stress and treated with agonists pan and C1 showed improved corneal barrier function, while C1 also increased GC density. NanoString analyses revealed upregulation of specific mRNA transcripts (Ptger4, Tnfaip3, Il1a and Ptger4, Tlr3, Osal1) in pan and C1 treated corneas compared to vehicle-treated corneas. Western blots showed pan and C1 decreased vehicle-induced NFkB nuclear translocation after DS for one day and increased EP4 and TNFAIP3 protein levels after five days of DS in corneal epithelium lysates. These results were confirmed by immunostaining. We conclude that small-molecule agonists of Trk receptors improve DED by decreasing NFkB activation and increasing protein expression of anti-inflammatory molecules TNFAIP3 and EP4. Surprisingly, the most efficacious small molecule agonists were not TrkA selective but TrkC and panTrk, suggesting that wider exploration of TrkB and C and pan Trk agonists are warranted in efforts to treat DED.